Fiscal policy and intranational risk-sharing - Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1998)
A general feature of national fiscal systems is that they provide buffers against regional fluctuations in output and employment by redistributing income between the different regions of a country. Recent literature in connection with European monetary integration has stressed the insurance aspect of this function: Through the fiscal system, regions obtain insurance against asymmetric shocks. In this paper, we review the literature on risk-sharing through fiscal mechanisms. While consumption smoothing would call for full risk-sharing among regions, moral hazard problems, political economy problems and considerations of macro economic stabilization reduce the optimal degree of risk sharing. This may explain why empirical research generally finds that intranational risk-sharing based on fiscal policy seems rather modest.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Finanzausgleich; Konjunkturpolitik; Schock; Eingebauter Stabilisator